(untitled) (Sciences & Technology. A, exactes sciences, 2017)
The addition of inorganic fertilizers to treat crop soil and increase its production has become a necessity and tool around the world. These various fertilizers, such as NPK fertilizers (Nitrogen, phosphate and potassium), cause an increase in the content of radionuclides in the essential nutrients by moving them from the soil to different parts of plants. Consequently, the activity concentration of some fertilizers used in the field of agriculture in the province of Constantine was measured using high resolution gamma ray spectrometry, in order to evaluate the radiation risk and its effect on human health.